International webinar on "Applied Mechanics for Engineers" / Nor Aziyah Bakhari and Mohd Rozaiman Aziz - Bakhari, Nor Aziyah; Aziz, Mohd Rozaiman (UiTM Global @ Office of International Affairs, 2024)
The webinar speaker. took place from 1:30 pm to 2:30 pm (MYT) or 11:00 am to 12:00 pm (IST). A total of 80 participants, including faculty members and students specialising in mechanical engineering, attended the event. Among them, 51 were from Mangayarkarasi College of Engineering (MCE), and 29 were external participants representing institutions such as SIT Engineering College, Vaigai Engineering College, AAA College of Engineering, SRM College of Engineering, SACS MAVMM Engineering College, and Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia.